Recognizing hypokalemic periodic paralysis in the differentials of acute flaccid paralysis: A case-based approach (Indian Journal of Case Reports, 2025)
Hypokalemic periodic paralysis (HypoPP) is a rare but important cause of acute flaccid paralysis that may be easily overlooked during initial evaluation. Timely recognition is essential, as management differs significantly from other neurological or metabolic causes of weakness. We report the case of a 51-year-old male who presented with an acute onset of flaccid quadriparesis. Despite initial treatment, the patient exhibited persistently low serum potassium levels, which did not respond adequately to standard potassium replacement. This unusual biochemical profile, combined with the clinical picture, led to a focused diagnostic approach that confirmed HypoPP. This case highlights the importance of including HypoPP in the differential diagnosis of acute flaccid paralysis, especially in patients with recurrent or persistent hypokalemia. Early identification and appropriate management can significantly alter patient outcomes and are essential to establish appropriate long-term management strategies to prevent recurrent episodes.